Eficacia de las movilizaciones Neuromeningeas en Lumbociatalgia para pacientes con dolor radicular que acuden al hospital básico militar 11 B.C.B “Galápagos” de la Ciudad de Riobamba en el periodo abril – septiembre 2016. - Ramírez Ramírez, Karla Virginia (2017)
This was a field research with the aim to determine the “EFFICACY OF NEUROMENING MOVILIZATIONS IN LUMBOCIATALGIA FOR PATIENTS WITH RADICULAR PAIN AT THE MILITAR BASIC HOSPITAL 11 BCB “GALAPAGOS” OF RIOBAMBA CITY IN THE PERIOD APRIL-SEPTEMBER 2016”. Neuronemingeas mobilizations is a non-invasive technique that is based on the nervous system managing to mobilize neural structures by means of movements realizing a neural tension, which allows an improvement of the skeletal muscle system helping the patient to reduce the symptomatology. The population was 30 people with diagnosis of lumbar pain using clinical histories, which were evaluated at the beginning and at the end of the treatment applying the EVA scale, Laségue test and test of Slump. According to the data obtained it was evidenced a greater tendency of efficiency on severe pain with respect to the initial pain. Regarding the final pain index, it was evident that at the end of the treatment the pain was reduced, proving that the neuromenical mobilizations are effective in lumbar pain for patients with radicular pain.